Exploring the excited-state charge transfer fluorescence profile of 7-hydroxycoumarin and 2-methylimidazole – a combined X-ray diffraction and theoretical approach. Issue 21 (18th May 2022) - Hawkins, Bryson A.; Najib, Elias; Du, Jonathan J.; Lai, Felcia; Platts, James A.; Groundwater, Paul W.; Hibbs, David E.
Abstract : This study investigated and rationalised the fluorescence modulation of 7-hydroxycoumarin in response to changing concentrations of 2-methylimidazole using low-cost quantum mechanical calculations from single crystal X-ray geometries. Abstract : This study investigated the effect of 2-methylimidazole (2-MIM) addition on the fluorescence of ethyl-7-hydroxy-2-oxo-2 H -chromene-3-carboxylate using low-cost density functional theory (DFT) and Time-Dependent DFT calculations on single crystal X-ray geometries of ethyl-7-hydroxy-2-oxo-2 H -chromene-3-carboxylate hydrate (1 ), 2-MIM (2 ), and the 1 : 1 co-crystal of (1 ) and (2 ), (3 ). At low concentrations (1 : 1–1 : 10) of 2-MIM, the fluorophore shows a decrease in the fluorescence intensity, but at higher concentrations (above 1 : 10) the fluorescence excitation maximum shifted from 354 nm to 405 nm, with a significant emission intensity increase. The changed excitation and emission profile at high concentrations is due to the deprotonation of the coumarin's phenolic group, which was confirmed by the increased shielding of the aromatic protons in the titration 1 H NMR spectra. The experimental fluorescence data between the 1 : 1 and 1 : 10 ratios agreed with the theoretical fluorescence data, with a redshift and decreased intensity when comparing (1 ) and (3 ). The data indicated that combining the fluorophore with 2-MIM increased levels of vibronic coupling between 2-MIM and the fluorophore decreasing de-excitation efficiency. These increased vibronic changes were due to charge transfer between the fluorophore and 2-MIM in (3 ). The subtle movement of the proton, H(5) toward N(2′) (0.07 Å) caused a significant decrease in fluorescence due to electron density distribution (EDD) changes. This was identified by comparison of the EDD in the excited (S1 ) and ground (S0 ) states plotted as an isosurface of EDD difference. For the higher concentrations, an alternative excitation pathway was explored by modifying the crystal geometry of (3 ) based on 1 H NMR spectroscopy data to resemble excitoplexes. Theses excitoplex geometries reflected the fluorescence profile of the fluorophore with high concentrations of 2-MIM; there were dramatic changes in the theoretical fluorescence pathway, which was 100% vibronic coupling compared to 15.31% in the free fluorophore. At this concentration, the de-excitation pathway causes remodelling of the lactone ring via stretching/breaking the CO bond in the S1 causing increased fluorescence by movement of the transition dipole moment. These results reflect previous studies, but the methods used are less experimentally and computationally expensive. This study is among the first to explain charge transfer fluorescence using crystalline geometries. This study will be of interest to the fields of crystal engineering and fluorescence spectroscopy.